The Effects of Movement Pattern Modification on Lower Extremity Kinematics and Pain in Females with Patellofemoral Pain - Salsich, Gretchen B. (J Orthop Sports Phys Ther, 2012)
STUDY DESIGN: Controlled laboratory study OBJECTIVES: To compare hip and knee kinematics and pain during a single limb squat between 3 movement conditions (‘usual’, ‘exaggerated’ dynamic knee valgus, ‘corrected’ dynamic knee valgus) in females with patellofemoral pain. BACKGROUND: Altered kinematics (increased hip adduction, hip medial rotation, knee abduction, and knee lateral rotation, collectively termed “dynamic knee valgus”) have been proposed to contribute to patellofemoral pain, however cross-sectional study designs prevent interpreting a causal link between kinematics and pain. METHODS: Twenty females with patellofemoral pain who demonstrated observable dynamic knee valgus performed single limb squats under ‘usual’, ‘exaggerated’, and ‘corrected’ movement conditions. Pain during each condition was assessed using a 0-100 mm visual analog scale. Hip and knee frontal and transverse plane angles at peak knee flexion and pain levels were compared using repeated measures, 1-way ANOVAs. Within condition associations between kinematic variables and pain were determined using Pearson correlation coefficients. RESULTS: In the ‘exaggerated’ compared to the ‘usual’ condition, increases were detected in hip medial rotation (mean +/-SD, 5.8±3.2°, P<.001), knee lateral rotation (5.5±4.9°, P<.001), and pain (8.5±10.8mm, P=.007). In the ‘corrected’ compared to the ‘usual’ condition, decreases were detected in hip adduction (3.5±3.7°, P=.001) and knee lateral rotation (1.6±2.8°, P=.06; however, average pain was not decreased (1.2±14.8mm, P=1.0). Pain was correlated with knee lateral rotation in the ‘usual’ (r=−0.47, P=.04) and ‘exaggerated’ (r=−0.49, P=.03) conditions. In the ‘corrected’ condition, pain was correlated with hip medial rotation (r=0.44, P=.05) and knee adduction (r=0.52, P=.02). CONCLUSION: Avoiding dynamic knee valgus may be an important component of rehabilitation programs in females with patellofemoral pain, as this movement pattern is associated with increased pain.